Semantics of innovations in modern German poetic discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Denominating certain objects, people differentiate and classify an objective world according to the most significant features. Individual and original nominations in poetry give an opportunity to reconstruct a linguistic image, identify a lexical-semantic value of word formation subsystem, and define semantic spheres of usage of language units. The purpose of our study is to analyze semantics of innovations in modern German Bernhard Lierheimer’s avant-garde poems. A complex of interacting general scientific and special linguistic methods has been used for compassing the purpose, specifically, inductive and deductive methods, analysis and synthesis, structural and semantic, logical and semantic, contextual, and comparative methods. Principal findings of the study comprise specification of the definition “innovation”, highlighting specific and borrowed new-formed elements, structural and genetic peculiarities of the phenomenon, “parts of speech” division in a verbal fabric of content and factual materials, a lexical and semantic classification of studied language units. As the findings of the study following conclusions were drawn: semantics of new nominations reflects author and persona’s encyclopaedic knowledge, their original way of thinking, a new philosophical view of nature and human-being, represents a semantic shift in an objective and an associative world. Both an objective and an associative world are structured in the limits of integrity and determined with sociocultural and psychological and aesthetic factors.
Keywords: neologism; semantic of the author’s neologism; the composite noun substantive; fully-formed composite; non-fully-formed composite